SRI: A Potential Water Saving technology for rice farmers - Mitra, Biplab; Mookherjee, Saikat; Biswas, Sujan (Indian Farming, 2015)
KVK Coochbehar revitalized farmers growing boro rice byintroducing SRI method by following various dissemination mechanisms including training and demonstration. This technology could increase the net profit on one hand and on the other hand could save irrigation water. Now there is a growing demand of SRI Marker and Cono weeder among the boro farmers of the district reflecting the acceptability of the technology among the farming community. Some local manufactures can be encouraged to develop such implements for better accessibility.